5 Quality Improvement Project (QIP): A Teamwork Approach to Optimise Fluid Intake in Older Inpatients #ButFirstADrink. (16th March 2021) - Vourliotis, N; Grimshaw, K; Harris, R
Abstract: The shortfalls of hydration management have been widely exposed since the Frances report in 2013. Age-related changes create challenges for people to drink adequate fluid amounts (Nazarko, 2018), making dehydration prevention in older people an ongoing public health priority (NICE, 2016). Hydration needs of older people are complex and may not be fully understood. A proactive MDT approach to facilitate regular drinking opportunities seems an achievable solution to increase hydration awareness, knowledge and daily fluid intake in older inpatients. A QI methodology was used, including stakeholder engagement and PDSA learning cycles to influence, engage and educate staff on hydration management. Outcome measures: Fluid intake (ml/day), number of drinks/days based on fluid balance chart recordings. Interventions: Sharing the #ButFirstADrink social media hydration movement, which includes educational posters, flyers and a YouTube video. Face to face drop-in education sessions were implemented using local hydration education resources from Age UK Salford and GM nutrition and hydration programme as teaching tools. SPC charts were used to show a time-series data. In 15 weeks, 461/525 fluid charts were reviewed from 169 patients. Mean age was 84 years and 68% females. Average daily fluid intake increased by 25% (exceeding aim) indicating 176mls more fluid was offered on average/day. Mean number of drinks/days increased from 4.6 to 6 post interventions. Knowledge and attitude improved in some areas; however fluid output is not routinely recorded. Post intervention, 89% of staff felt that offering a drink at first contact is a suitable hydration promotion campaign. The project scored 58% using the NHS sustainability model (ACT Academy, 2018) suggesting reason for optimism. As it is a behaviour change project, further engagement and momentum is dependent on ongoing enthusiasm to drive the #ButFirstADrink approach. This intervention is free, simple and innovative and stimulates behaviour change, raises drinking awareness and increases hydration.